The use of Popular Cultural Media in Spreading The Dakwah Message in Indonesia - Kusumaningtyas, AD. (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
The dakwah activities actually are focused on the delivering the dakwah message that contained the substance of Islamic teaching and its universal values. Dakwah nowadays, is not merely done through meeting in the majelis taklim congregations, sermons, and tabligh akbar (wide public meeting). But, it can be done also by some artists (arts workers) such as song writers, singers, authors, novelists, movie makers, etc. through their art work creations. Some art works such as music had inspired the public to accept the Islamic religious teaching through the songs they listened. And also the dakwah message can be well packaged by some novel writers so it touch the hearts of the readers. Not enough, the such book creations can also inspire the wider public through the movies and cinema creations, whether in televisions, movie cinema, even though advertisement movies. A da’i is encouraged to deliver the message of Islam creatively through various media, to meet the needs of the mad’u (targeted population of the message).